2022
DOI: 10.1111/jfpp.17178
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation for shelf‐stable and ready‐to‐eat shrimp chili paste

Abstract: Gamma irradiation was applied to extend the shelf life of ready‐to‐eat shrimp chili paste stored at ambient temperature. Doses of 2–8 kGy did not affect aw, pH, color, and antioxidant properties of shrimp chili paste. Noticeable change in TBARs was noticed at 4 kGy, but panelists gave similar sensorial acceptability scores among samples. Gamma irradiation at 4 kGy could completely eliminate Escherichia coli intentionally inoculated in shrimp chili paste. However, gamma irradiation at 8 kGy was recommended beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Fungal contamination rates were lower in garlic and ginger samples due to antifungal activity (Hammami et al, 2014). A similar study reported that the optimum gamma irradiation dose was 5 kGy in spices like red chili, turmeric, coriander, and cumin powder (Sirisoontaralak et al, 2022). A recent study also found that a 5 kGy dose could stop the growth of fungi in spice samples (Esmaeili et al, 2018).…”
Section: Fungal Mycoflora In Non-irradiated and Irradiated Spice Samplesmentioning
confidence: 94%
“…Fungal contamination rates were lower in garlic and ginger samples due to antifungal activity (Hammami et al, 2014). A similar study reported that the optimum gamma irradiation dose was 5 kGy in spices like red chili, turmeric, coriander, and cumin powder (Sirisoontaralak et al, 2022). A recent study also found that a 5 kGy dose could stop the growth of fungi in spice samples (Esmaeili et al, 2018).…”
Section: Fungal Mycoflora In Non-irradiated and Irradiated Spice Samplesmentioning
confidence: 94%